Changes in mortality of Polish residents in the early and late old age due to main causes of death from 2000 to 2019 - Monika Burzyńska; Małgorzata Pikala (Frontiers Media S.A., 2023)
PurposeThe aim of the study was to assess mortality trends in Poland between 2000 and 2019 in the early and late old age population (65-74 years and over 75 years).MethodsThe work used data on all deaths of Polish residents aged over 65 years (N = 5,496,970). The analysis included the five most common major groups of causes of death: diseases of the circulatory system, malignant neoplasms, diseases of the respiratory system, diseases of the digestive system and external causes of mortality. The analysis of time trends has been carried out with the use of joinpoint models. The Annual Percentage Change (APC) for each segments of broken lines, the Average Annual Percentage Change (AAPC) for the whole study period (95% CI), and standardized death rates (SDRs) were calculated.ResultsThe percentage of deaths due to diseases of the circulatory system decreased in all the studied subgroups. Among malignant neoplasms, lung and bronchus cancers accounted for the largest percentage of deaths, for which the SDRs among men decreased, while those among women increased. In the early old age, the SDR value increased from 67.8 to 76.3 (AAPC = 0.6%, p > 0.05), while in the late old age group it increased from 112.1 to 155.2 (AAPC = 1.8%, p < 0.05). Among men, there was an upward trend for prostate cancer (AAPC = 0.4% in the early old age group and AAPC = 0.6% in the late old age group, p > 0.05) and a downward trend for stomach cancer (AAPC −3.2 and −2.7%, respectively, p < 0.05). Stomach cancer also showed a decreasing trend among women (AAPC −3.2 and −3.6%, p < 0.05). SDRs due to influenza and pneumonia were increasing. Increasing trends in mortality due to diseases of the digestive system in women and men in the early old age group have been observed in recent years, due to alcoholic liver disease. Among the external causes of mortality in the late old age group, the most common ones were falls.ConclusionsIt is necessary to conduct further research that will allow to diagnose risk and health problems of the elderly subpopulation in order to meet the health burden of the aging society.